2019
DOI: 10.1002/app5.296
|View full text |Cite
|
Sign up to set email alerts
|

Dependency on Australian aid and the introduction of inclusive education initiatives in Kiribati

Abstract: This study examines dependency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, the existing research on international education cooperation frequently overlooks the examination of the education systems of donor and recipient countries. Instead, it solely focuses on evaluating the effectiveness of international cooperation policies (Chung & Park, 2013;Lei & Myers, 2011;Yates, 2020). To gain a more holistic understanding, considering the nuances of inclusive education within individual donor and recipient countries, including perspectives and approaches toward international cooperation, is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing research on international education cooperation frequently overlooks the examination of the education systems of donor and recipient countries. Instead, it solely focuses on evaluating the effectiveness of international cooperation policies (Chung & Park, 2013;Lei & Myers, 2011;Yates, 2020). To gain a more holistic understanding, considering the nuances of inclusive education within individual donor and recipient countries, including perspectives and approaches toward international cooperation, is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed a growing body of publications on the implementation of inclusive education (IE) in the Pacific Islands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The major themes emerging from these studies include the need for reconceptualising IE to develop culturally and contextually informed policies, the importance of school leadership for the successful implementation of IE and generally raising awareness and advocacy for people living with disabilities. In contrast, there is very little in the audiology literature from low-and middleincome countries (LMICs) on the knowledge and attitudes of key stakeholders towards IE for students with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
“…According to researchers, it is a well-established fact that there are impaired students in higher education, hence it is necessary to update the instructional strategies and resources [2]. However, according to recent studies, some governments continue to oppose the inclusion of disabled students [3]. These oppositions are primarily caused by historical reluctance to involve in familiar concerns and decisions, a lack of funding for anything other than the most basic educational needs, and a continued refusal to acknowledge the advantages of educating students with disabilities.…”
Section: Introductionmentioning
confidence: 99%